UNDERSTANDING THE GENDER AND FEMINIST INTERPRETATION CONSTRUCTIONIN INDONESIA - Nafsih, Syarifatun (Kafa`ah: Journal of Gender Studies, 2023)
The differences in biological anatomy between men and women are pretty straightforward, but the problem is the effects caused by these sex differences. The issue of differences is what then causes much debate in various circles. Biological sex differences (sex) formed through the body's anatomy also give rise to several types of judgments in the framework of thinking, which are then carried over to the behavior of everyday life, the behavior of society (customs), religion, and even the country. That cultural interpretation is then understood as gender. The structure, the social system of society, and even some interpretations that tend to be patriarchal further strengthen the ideology of society, which creates injustice for women. Ultimately, this condition is realized by women as a condition that imprisons them in a social downturn. Then a women's movement emerged, which claimed to be a feminist movement to fight for the fate of women. Because of this, there is also an interpretation from a feminist point of view. Using qualitative methods, and literature review, researchers want to explain how gender is understood and the construction of feminist interpretations in Indonesia. This is important to know the development of interpretation related to gender in Indonesia. Feminism, especially in Islam, is not a movement of rebellion against men but an understanding that wants to respect women. There is no discrimination, Marginalization, or subordination. Studies from a feminist point of view in Indonesia have continued to develop to date.